Peluang Redefinisi Kewenangan Pembentukan Perppu dalam RUU Lembaga Kepresidenan - Rahadian Diffaul Barraq Suwartono (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
The President's authority to form a Government Regulation in Lieu of Laws, as stated in Article 22 of the 1945 Constitution of the Republic of Indonesia, has recently received more and more criticism and academic review. Recent research shows that a redefinition is needed, or at least a limitation on the scope of "exigencies compel" as an indicator of the activation of the President's authority to form a Government Regulation in Lieu of Laws. Because, from time to time, there has been a misleading practice which has caused legal chaos when the President exercises the authority to form a Government Regulation in Lieu of Laws. This article highlights the opportunity for more concrete regulation, or at least limitations, on interpreting the meaning of "compelling urgency" as the entry point for implementing a Government Regulation in Lieu of Laws. Using a legal policy and conceptual approach, this article focuses on answering research questions such as: how is the development of science regarding criticism of the formation of a Government Regulation in Lieu of Laws by the President in Indonesia; and is it possible to further regulate the redefinition of the authority to form a Government Regulation in Lieu of Laws through the Presidential Law. This article aspires to a more critical understanding of the granting of the authority to form a Government Regulation in Lieu of Laws in Indonesia. Therefore, the proposal to reconceptualize the authority to form a Government Regulation in Lieu of Laws through the legislative discourse of the Presidential Law needs to be submitted.